2012
DOI: 10.1002/jemt.21021
|View full text |Cite
|
Sign up to set email alerts
|

Topography of four different endodontic rotary systems, before and after being used for the 12th time

Abstract: Root canal preparation may damage NiTi instruments resulting in wear and deformation. The aim of this study was to make a comparative evaluation of the surface topography of the cervical third of four different rotary systems, before and after being used twelve times, in 1.440 resin blocks with simulated root canals with standardized 45° curvatures, and analyzed by atomic force microscopy AFM. The blocks were divided into four groups and prepared according to the manufacturers recommendations: Group 1--K3®; Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 18 publications
1
33
1
Order By: Relevance
“…, Yamazaki‐Arasaki et al . ). Thus, it is unreliable to determine the surface irregularities of solution‐immersed files caused by irrigation.…”
Section: Discussionmentioning
confidence: 97%
“…, Yamazaki‐Arasaki et al . ). Thus, it is unreliable to determine the surface irregularities of solution‐immersed files caused by irrigation.…”
Section: Discussionmentioning
confidence: 97%
“…The microcavities after use may be associated with loss of Ni and Ti atoms (22). The chemical composition and geometry of NiTi alloys has a binary intermetallic and equiatomic bonding force between Ni and Ti (22), which may be changed by a thermodynamic process, or/and when submitted to certain stress, as root canal preparation (23).…”
Section: Discussionmentioning
confidence: 99%
“…The safe clinical use of the "single use" Reciproc and WaveOne instruments for shaping multi-rooted teeth has been discussed. According to Yamazaki-Arasaki et al, 30 the single use of reciprocating instruments can actually refer to the use in three or four root canals of the same molar or of the same patient. Nevertheless, it was previously reported that although both instruments can be used in 3-4 root canals, the canals can be complex and tortuous, increasing fatigue.…”
mentioning
confidence: 99%